Static posturography as an instrument to assess the balance among athletes - Ewelina Stefania Pankanin; Anna Maria Dobosiewicz; Paulina Miętkowska (Kazimierz Wielki University, 2018)
Equilibrium is defined as the ability to maintain the roll centre of gravity (centre of mass - COM), which is located in the abdomen, inner support surface defined by the contour of the foot. The process to maintain standing balance involves continuous loss of balance and recovery [1]. The balance is considered to be the basic motor skills and is especially important for athletes. Examination of postural balance is a troublesome scientific issue, but static posturography allows for a reliable assessment of this aspect.